Fragrant Sesquiterpene Ketones as Trace Constituents in Frankincense Volatile Oil of Boswellia sacra - Niebler, Johannes; Zhuravlova, Katharina; Minceva, Mirjana; Büttner, Andrea (Journal of Natural Products, 2016)
In a previous study, two highly potent yet unidentified odorants were detected that were present at trace levels in the volatile fraction of Boswellia sacra gum resin. These two compounds were isolated semipreparatively from the volatile oil by a sensory-guided fractionation process involving microscale bulb-to-bulb distillation, countercurrent chromatography, and preparative gas chromatography. In this manner, the two oxygenated sesquiterpenes could be identified as rotundone (1) and mustakone (2). Compound 2 is described for the first time as a potent odorant with a very low odor threshol

Frankincense Revisited, Part I: Comparative Analysis of Volatiles in Commercially Relevant Boswellia Species - Niebler, Johannes; Büttner, Andrea (Chemistry & Biodiversity, 2016)
The genus Boswellia comprises a number of species which are famous for their production of frankincense, a fragrant gum resin. In the published literature, manifold studies on the volatiles and semivolatiles in individual samples of these gum resins exist, yet very few studies have investigated multiple samples. Contradictory results with regard to the volatile composition exist in literature. In this first part of the study, a large sample set (n=46) of mostly commercially obtained gum resins and essential oils was investigated by solid phase micro-extraction gas chromatography-mass spectrometry (SPME-GC-MS) or GC-MS. In the four commercially relevant species, namely B. sacra, B. serrata, B. papyrifera and B. frereana, 216 compounds were identified or tentatively identified, and the statistical evaluation of the resulting chemical profiles allowed a clear distinction between the species by their volatile profile. With only few exceptions, the designated species was found to be in accordance with the composition reported in reliable literature sources and detected in botanically identified samples. Chemotaxonomic marker substances were suggested to facilitate the differentiation of commercial gum resins or essential oils based on their volatile profil
Keywords: Boswellia; Burseraceae; Frankincense; Olibanum; SPME-GC-MS; Essential oil

Frankincense Revisited, Part II: Volatiles in Rare Boswellia Species and Hybrids - Niebler, Johannes; Eslamieh, Jason; Büttner, Andrea (Chemistry & Biodiversity, 2016)
In this second part of the investigation of volatiles and semivolatiles in Boswellia gum resins, an additional five less common species were analyzed by (SPME-)GC-MS, namely B. ameero, B. elongata, B. neglecta, B. popoviana and B. rivae. Moreover, the results of hybridization experiments are reported in combination with the volatile composition of their gum resins. Our study shows that B. sacra benefits from an intra-specific cross-pollination, as the resulting hybrid B. sacra var. supersacra has a far higher seed germination rate and viabilit
Keywords: Boswellia; Burseraceae; Hybrid; Frankincense; Olibanum; SPME-GC-MS

Identification of odorants in frankincense (Boswellia sacra Flueck.) by aroma extract dilution analysis and two-dimensional gas chromatography-mass spectrometry/olfactometry. - Niebler, Johannes; Büttner, Andrea (Phytochemistry, 2015)

Identification of potent odorants in frankincense (Boswellia sacra) by aroma extract dilution analysis and two-dimensional gas chromatography-olfactometry - Niebler, Johannes; Büttner, Andrea (Phytochemistry, 2015)
Frankincense has been known, traded and used throughout the ages for its exceptional aroma properties, and is still commonly used in both secular and religious settings to convey a pleasant odor. Surprisingly, the odoriferous principle(s) underlying its unique odor profile have never been published. In this study, resin samples of Boswellia sacra Flueck. from both Somalia and Oman were investigated by aroma extract dilution analysis. In a comprehensive, odor-activity guided approach both chemo-analytical and human-sensory parameters were used to identify odor active constituents of the volatile fraction of B. sacra. Among the key odorants found were α-pinene, β-myrcene, linalool, p-cresol and two unidentified sesquiterpenoids. Overall, a total of 23 odorants were detected and analyzed by gas chromatography-olfactometry and heart-cut two-dimensional gas chromatography-mass spectrometry/olfactometry. The majority of the identified odorant compounds were oxygenated monoterpenes, along with some relevant mono- and sesquiterpenes and only one diterpenoid substance. Several of these compounds were reported here for the first time as odorous constituents in B. sacra. Identifying bioactive compounds might support a better understanding with regard to the potential benefits of frankincense, for example in aromatherapy or ecclesial settings.
UnivIS-Import:2015-03-09:Pub.2015.nat.dchph.llmch.identi
Keywords: Aroma extract dilution analysis; Boswellia carteri Birdw.; Boswellia sacra Flueck.; Burseraceae; Frankincense; Gas chromatography–olfactometry; Heart-cut two-dimensional gas chromatography–mass spectrometry/olfactometry; Odorants; Terpenes

Metathetic sulfur transfer mediated by N-(2-aminophenyl)-4-methyl-thiazolin-2-thione derivatives: Part III: a new route to diversely substituted S-alkyl thioesters - Mehdid, Mohammed Amine; Djafri, Ayada; Andreoli, Federico; Vanthuyne, Nicolas; Farran, Daniel; Niebler, Johannes; Büttner, Andrea; Giorgi, Michel; Roussel, Christian (Tetrahedron, 2013)
A metal free synthesis of S-alkyl thioesters, which does not involve alkylthiol or thiocarboxylic acid as sulfur source is disclosed. The process involves first an acylation at the nitrogen of the readily available N-(2-aminophenyl)-4-methyl-thiazolin-2-thione, second an alkylation at sulfur of the resulting amides and finally a base catalyzed metathetic reaction, which provides under very mild conditions and in high isolated yields the S-alkyl thioesters. An ion-pair intermediate (9-acyl-3-methyl[1,3]thiazolo[3,2-a][3,1]benzimidazol-9-ium alkylthiolate) accounts for the formation of mixed thioesters during cross-coupling experiments. S-Alkyl diversity is provided by the alkylating agent and the acyl diversity comes from the acylating agent, while the sulfur atom is provided by the heterocycle.
UnivIS-Import:2015-03-09:Pub.2013.nat.dchph.llmch.metath
Keywords: Sulfur transfer; Heterocycle; Acylation; Alkylation; Thiazolium salts

Metathetic Sulfur Transfer mediated by N-(2-aminophenyl)-4-methyl-thiazolin-2-thione derivatives: Part III: a new Route to Diversely Substituted S-alkyl thioesters. - Mehdid, Mohammed Amine; Djafri, Ayada; Andreoli, Federico; Vanthuyne, Nicolas; Farran, Daniel; Niebler, Johannes; Büttner, Andrea; Giorgi, Michel; Roussel, Christian (Tetrahedron, 2013)
A metal free synthesis of S-alkyl thioesters, which does not involve alkylthiol or thiocarboxylic acid as sulfur source is disclosed. The process involves first an acylation at the nitrogen of the readily available N-(2-aminophenyl)-4-methyl-thiazolin-2-thione, second an alkylation at sulfur of the resulting amides and finally a base catalyzed metathetic reaction, which provides under very mild conditions and in high isolated yields the S-alkyl thioesters. An ion-pair intermediate (9-acyl-3-methyl[1,3]thiazolo[3,2-a][3,1]benzimidazol-9-ium alkylthiolate) accounts for the formation of mixed thioesters during cross-coupling experiments. S-Alkyl diversity is provided by the alkylating agent and the acyl diversity comes from the acylating agent, while the sulfur atom is provided by the heterocycl

Pyrolysis-GC-MS-Olfactometry: A new approach to identify thermally generated odorants in frankincense - Niebler, Johannes; Büttner, Andrea (Journal of Analytical and Applied Pyrolysis, 2015)
Abstract Pyrolysis-GC-MS coupled with olfactometric detection represents a promising new instrumental approach for observing the generation of odor-active compounds from the non-volatile fraction of complex sample materials. The possibility to eliminate the volatiles already present in the sample by a thermal desorption prior to pyrolysis is particularly beneficial with the use of a filament-type pyrolyser. This is exemplified by an investigation of frankincense, the resin of Boswellia sacra Flueck. A variety of thermally generated odor active substances, absent in the native material, could be detected by this approach, which would otherwise be covered by volatiles from the sample material. A fractionation of the material by solvent extraction and high vacuum distillation allowed to further narrow down the origin of the pyrolytically generated compounds. Additionally, repeated thermal desorption at mounting temperatures from 120 to 300 °C followed by a pyrolysis run at 500 °C monitored the release and generation of compounds from the sample. This new approach is highly efficient and convenient not only for the investigation of incense materials, but also for off-odor generation in thermally strained materials, investigation of smoke flavor generation and related topics.
UnivIS-Import:2015-07-08:Pub.2015.nat.dchph.llmch.pyroly
Keywords: Boswellia; Frankincense; Incense burning; Odor; Olfactometry; Py-GC-MS

Pyrolysis-GC–MS–Olfactometry: A new approach to identify thermally generated odorants in frankincense. - Niebler, Johannes; Büttner, Andrea (Journal of Analytical and Applied Pyrolysis, 2015)